2019
DOI: 10.21522/tijph.2013.07.02.art008
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study on Hand Hygiene Practices Among Health Care Workers at Infectious Diseases Hospital Kano, Nigeria

Abstract: Background: Effective hand hygiene is essential for reducing healthcare associated infections. However, compliance of healthcare workers to hand hygiene guidelines are reportedly poor. It is important therefore to instill adequate knowledge and good attitudes and practices at the time of primary training of the healthcare workers. The aim of the study was to assess hand hygiene practices among healthcare workers in Infectious Diseases Hospital Kano, Nigeria. It was hoped that the study would benefit all health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“… 10 Besides, Imai and colleagues 22 argued that older age correlates with an increased ability to cope with emergencies related to infectious diseases. On the contrary, Aliyu and colleagues 23 found good IPC practices among younger HCWs before the COVID-19 pandemic in Nigeria, while Mitchell and colleagues 24 did not find any relationship with age or sex. We found female HCWs to be more compliant with IPC guidance than their male counterparts.…”
Section: Discussionmentioning
confidence: 88%
“… 10 Besides, Imai and colleagues 22 argued that older age correlates with an increased ability to cope with emergencies related to infectious diseases. On the contrary, Aliyu and colleagues 23 found good IPC practices among younger HCWs before the COVID-19 pandemic in Nigeria, while Mitchell and colleagues 24 did not find any relationship with age or sex. We found female HCWs to be more compliant with IPC guidance than their male counterparts.…”
Section: Discussionmentioning
confidence: 88%
“…This shows that completing the task is more important than performing hand hygiene. For Yildirim et al, (2008) as cited by Aliyu et al, (2019) [1] reported that adherence to recommended handwashing practices remains unacceptably low, rarely exceeding of situations in which hand hygiene is indicated. The current results further revealed that nursing students were non-compliant on recommended situations where handwashing is needed.…”
Section: Resultsmentioning
confidence: 99%
“…There are quite a number of studies on hand hygiene practices in developing countries. A study carried out at the Infectious Disease Hospital, Kano, showed that time spent washing hands by health care workers was 12.36% of the 40-60 seconds recommended by WHO (20-30 seconds if using an alcohol-based hand rub) with only 28% of nurses and 23% of doctors following hand hygiene practices (Aliyu, 2019). A similar study carried out in Babcock University Teaching Hospital, Nigeria, revealed an overall compliance of 32.5% (Shobowale, Onyedibe, Adegunle, Elikwu, 2017).…”
Section: Introductionmentioning
confidence: 99%